Juvenile deliquency and law enforcement in the Philippines a case of private security law enforcement regarding juvenile delinquency in SM City Iloilo and marymart Center. - Otico, Maria Lea Bernadeth S.
The private sector has been a big factor in law enforcement. This research project studied the practice of private security officers stationed in two malls in Iloilo city which are involved in the apprehension of juvenile delinquents in these malls. It examines factors such as social disorganization, organizational structure, training and the general views of the law enforcers towards juvenile delinquents that can affect the way private security guards deal with juvenile delinquents that can affect the way private security guards deal with juvenile delinquents that they can apprehend. We conclude that among these factors, mall structure and training affect how security officers from SM City Iloilo deal with juvenile delinquents; while their personal views regarding juvenile delinquents is the primary factor that affects how security guards from Mary Mart Center deal with juvenile delinquents during their posts.